Analisis Implementasi Kebijakan Program Makan Bergizi Gratis di Kota Jambi Menurut Teori Implementasi Kebijakan Merilee S. Grindle - Septiana Louisa Silaban; Sutri Destemi Elsi; Dimas Rizal (Demokrasi: Jurnal Riset Ilmu Hukum, Sosial dan Politik, 2026)
Makan Bergizi Gratis (MBG) program is a national policy designed to improve the nutritional quality of children and support human resource development. However, its implementation at the regional level still faces various institutional and coordination issues. This study aims to analyze the implementation of the Free Nutritious Meals program in Jambi City, focusing on the dynamics of program implementation and the inhibiting factors. This study uses a qualitative approach with a case study method. Data were collected through in-depth interviews with policy implementers and  documentation with informants determined through purposive sampling. Data analysis was conducted using Merilee S. Grindlee policy implementation theory through data reduction, presentation, and conclusion drawing. The results of the study indicate that the implementation of the MBG program in Jambi City has not been running optimally. This condition is characterized by the strong dominance of the central government in the decision making process, weak coordination between actors at the regional level, and inadequate readiness of supporting institutions, especially in aspects of human resources, monitoring system, and clarity of operational standards for implementation.